Death of the public university? : uncertain futures for higher education in the knowledge economy - Wright, Susan, 1951-; Shore, Cris, 1959- (Higher education in critical perspective : practices and policies, 2017)
"Universities have been subjected to continuous government reforms since the 1980s, to make them 'entrepreneurial', 'efficient' and aligned to the predicted needs and challenges of a global knowledge economy. Under increasing pressure to pursue 'excellence' and 'innovation', many universities are struggling to maintain their traditional mission to be inclusive, improve social mobility and equality and act as the 'critic and conscience' of society. Drawing on a multi-disciplinary research project, University Reform, Globalisation and Europeanisation (URGE), this collection analyses the new landscapes of public universities emerging across Europe and the Asia-Pacific, and the different ways that academics are engaging with them"--